International Capital Mobility, Shadow Prices and the Cost of Protection. - Neary, J; Ruane, F (CEPR, 1985)
This paper studies the welfare losses from tariff protection in a general model of a small open economy where some factors are internationally mobile. It is shown that, as long as the economy remains incompletely specialised international factor mobility must raise the cost of protection. This result is illustrated in the context of the specific-factors and Heckscher-Ohlin models. In addition, we examine its relationship to earlier work on immiserising capital inflows and on negative shadow prices for factors of production. This allows us to synthesise a number of recent results within a common framework.